Analisis Pemanfaatan Media Penyiaran dalam Diseminasi Nilai-Nilai Keagamaan Islam: Studi Kasus Program Islam Itu Indah di TRANSTV - Rahman Hakim, Hari; Hidayah, Arina Rohmatul; Alisya, Mia; Khairunnisa, Khairunnisa; Bayu, Bayu (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research examines the utilization of broadcast media in disseminating Islamic religious values through a case study of the program